Detection and some properties of a high molecular weight toxin in the hypobranchial gland of strawberry conch Strombus luhuanus. (October 2015) - Abiko, Keisuke; Iwayama, Ayane; Shiomi, Kazuo
Abstract: The extract from the hypobranchial gland of strawberry conch Strombus luhuanus was found to be lethal to mice. There were no marked regional and seasonal variations in toxicity although a considerable individual variation was recognized. The toxin was thermostable and extractable with aqueous solvents but not with organic solvents. Behaviors in dialysis, ultrafiltration and column chromatography on various adsorbents suggested that the toxin is a high molecular weight acidic substance of 400–500 k. Highlights: The hypobranchial gland of strawberry conch Strombus luhuanus was found to be toxic. The toxicity has a considerable individual variation but no regional and seasonal variations. The toxin is a high molecular weight acidic substance of 400–500 k.